Polymorphisms within autophagy-related genes influence the risk of developing colorectal cancer: a meta-analysis of four large cohorts - Sainz, Juan (2021)
The role of genetic variation in autophagy-related genes in modulating autophagy and cancer is poorly understood. Here, we comprehensively investigated the association of autophagy-related variants with colorectal cancer (CRC) risk and provide new insights about the molecular mechanisms underlying the associations. After meta-analysis of the genome-wide association study (GWAS) data from four independent European cohorts (8006 CRC cases and 7070 controls), two loci, DAPK2 (p = 2.19 × 10−5) and ATG5 (p = 6.28 × 10−4) were associated with the risk of CRC. Mechanistically, the DAPK2rs11631973G allele was associated with IL1 β levels after the stimulation of peripheral blood mononuclear cells (PBMCs) with Staphylococcus aureus (p = 0.002), CD24 + CD38 + CD27 + IgM + B cell levels in blood (p = 0.0038) and serum levels of en-RAGE (p = 0.0068). ATG5rs546456T allele was associated with TNF α and IL1 β levels after the stimulation of PBMCs with LPS (p = 0.0088 and p = 0.0076, respectively), CD14+CD16− cell levels in blood (p = 0.0068) and serum levels of CCL19 and cortisol (p = 0.0052 and p = 0.0074, respectively). Interestingly, no association with autophagy flux was observed. These results suggested an effect of the DAPK2 and ATG5 loci in the pathogenesis of CRC, likely through the modulation of host immune responses.